Investigating the mediating role of moral identity on the relationship between spiritual intelligence and Muslims" self-esteem - Boudlaie, Hasan (HTS teologiese studies, 2022)
One of the critical crises observed in human society, especially in the so-called advanced and industrial societies, is the spiritual crisis. Spirituality in various types of cultural and religious concepts is considered a spiritual path one in which can achieve something like a high level of consciousness, wisdom or union with God. In addition, self-esteem is a sense of worth. This feeling comes from the sum of our thoughts, feelings, emotions and experiences throughout life. Dignity also means honour and pride, which has been mentioned many times in the Qur’an. In contrast to dignity, there is humiliation, which means lack of dignity in which one simply accepts defeat. Religious teachings, especially Islamic teachings, do not summarise dignity as wealth, luxury and the enjoyment of material possibilities, but interprets dignity as spirituality, and liberation from the shackles of worldliness, which give Muslims a moral identity. The main purpose of this study is to investigate the mediating role of moral identity between spiritual intelligence and self-esteem of Muslims. The statistical population includes 834 Muslim employees working in 20 branches of one Iranian university. Necessary data were collected by standard questionnaires. Pearson’s correlation coefficient and regression analysis in SPSS software (Statistical Package for the Social Sciences) were used to analyse the data. According to the results of the analysis, there is a positive relationship between spiritual intelligence and self-esteem of Muslims. There is also a positive relationship between moral identity and self-esteem. Furthermore, moral identity plays a mediating role in the relationship between spiritual intelligence and self-esteem, and it strengthens this relationship.Contribution: The present study proves the mediating role of ethical identity on the relationship between spiritual intelligence and self-esteem in an Islamic society.